What Does Media Say about Mental Health: A Literature Review of Media Coverage on Mental Health - Hao Zhang; Amira Firdaus (Journalism and Media)
As global attention to mental health issues increases, its media portrayal becomes increasingly important. This literature review explores the representation of mental health in the media. The study found that the media plays a key role in shaping the public’s views on mental health issues. Positive media reports can help increase public awareness, reduce stigma, and promote help-seeking behaviors and policy improvements. However, negative reports may deepen misunderstandings and prejudices, increase stigma, and hinder people from seeking help. Several topics including violence and threats have become common themes in media reports on mental health issues. In addition, the portrayal of mental health on social media is emphasized, which provides a platform for discussing mental health issues, but also brings challenges to information authenticity and privacy protection. Social media interactions can provide support for mental health issues, but negative comments and cyberbullying may exacerbate the problem. The significance of this literature review is to provide theoretical support for improving media coverage and formulating public strategies, calling on media practitioners to report mental health issues in a responsible manner to promote healthier public attitudes and more effective policy interventions.